Private military and security companies (PMSCs) and the quest for accountability - Andreopoulos, George J.; Kleinig, John 1942- (Routledge, 2015)
his book critically examines the growing role of PMSCs in conflict and post-conflict situations, as part of a broader trend towards the outsourcing of security functions. Particular emphasis is placed on key moral, legal, and political considerations involved in the privatization of such functions, on the impact of outsourcing on security governance, and on the main challenges confronting efforts to hold PMSCs accountable through a combination of formal and informal, domestic as well as international, regulatory mechanisms and processes. It will be of interest to scholars, policymakers, practitioners and advocates for a more transparent and humane security order